2018
DOI: 10.1002/asia.201800681
|View full text |Cite
|
Sign up to set email alerts
|

A Porous Organic Poly(triphenylimidazole) Decorated with Palladium Nanoparticles for the Cyanation of Aryl Iodides

Abstract: A new porous organic poly(triphenylimidazole), PTPI-Me, was prepared through a Yamamoto self-coupling reaction of 2,4,5-tris-(4-bromophenyl)-1-methyl-1H-imidazole (TPI-Me) in the presence of bis(1,5-cyclooctadiene)nickel(0). The polymer was subsequently decorated with Pd nanoparticles (NPs) to afford a heterogeneous cyanation catalyst, Pd@PTPI-Me. Pd NPs with an average diameter of 2.7 nm were grown within the PTPI-Me framework, owing to the coordination of the imidazole rings to the Pd species. The resultant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Yu et al reported a synthesis of a new POP containing poly­(triphenylimidazole) (PTPI-Me) using a Yamamoto self-coupling reaction of 2,4,5-tris­(4-bromophenyl)-1-methyl-1Himidazole (TPI-Me) (Figure ). Triphenylimidazole has been chosen as a building block because of its rigidity and the presence of a nitrogen containing imidazole group, which can coordinate with metal ions and stabilize metal NPs. The porosity studies demonstrated that the polymer contains both mesopores and macropores in the broad range from 2 to 100 nm.…”
Section: Porous Polymersmentioning
confidence: 99%
“…Yu et al reported a synthesis of a new POP containing poly­(triphenylimidazole) (PTPI-Me) using a Yamamoto self-coupling reaction of 2,4,5-tris­(4-bromophenyl)-1-methyl-1Himidazole (TPI-Me) (Figure ). Triphenylimidazole has been chosen as a building block because of its rigidity and the presence of a nitrogen containing imidazole group, which can coordinate with metal ions and stabilize metal NPs. The porosity studies demonstrated that the polymer contains both mesopores and macropores in the broad range from 2 to 100 nm.…”
Section: Porous Polymersmentioning
confidence: 99%
“…POFs have been synthesized in large quantities and widely investigated in the CO 2 sorption field [ 13 , 14 , 15 , 16 ]. Up to now, various synthetic reactions have been explored in the preparation of POFs, including the Yamamoto reaction [ 17 ], the Sonogashira–Hagihara cross-coupling reaction [ 18 ], the Suzuki coupling reaction [ 19 ], oxidative coupling polymerization [ 20 ], and the Friedel–Crafts alkylation reaction [ 21 ]. Nevertheless, most polymerization reactions commonly require rigorous reaction conditions in the preparation of POFs, including high temperatures, expensive noble metal catalysts, and inert gas shielding.…”
Section: Introductionmentioning
confidence: 99%